Finland : Financial Sector Assessment Program: Technical Note-Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program (FSAP) for Finland in the area of banking supervision. The regulatory and supervisory framework for liquidity and funding risk has improved since the last FSAP, but certain vulnerabilities persist and require greater attention. Finnish banks continue to rely extensively on wholesale funding, as noted in the 2010 FSAP. Although supervisory action has managed to mitigate the problem, many banks remain heavily exposed to the risk of a dry-up of unsecured wholesale funding. Also, banks hold covered bonds issued by other banks as part of their liquidity buffer.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet